Milking the plains: movement of large dairy operations into southwestern Kansas - Harrington, Lisa M.B.; Lu, Max; Kromm, David E. (My University, 2010)
Western Kansas has an historical identification with cattle, with a focus on cattle ranching and more specifically since the 1950s, beef-cattle feedlots. Since the mid-1990s large dairy operations have moved into southwestern Kansas. Today more than twenty large dairies house more than 70,000 milk cows. These operate as confined feeding operations similar to beef-cattle feedlots. Regional advantages for the dairy industry include affordable land with wide-open space, local residents’ cattle- and dairy-friendly attitudes, and other factors. Regional promoters have actively recruited dairies, and a dairy-business support system has emerged. The prospects for continued expansion of dairies in southwestern Kansas are unclear; despite the locational advantages and the possibility that the industry may continue to relocate here, as did the cattle-feeding industry several decades ago, further moves into the area may depend on continued resources availability and additional infrastructure development.
Keywords: Agriculture; Cattle; Dairy; Farmers' attitude; Industrial restructuring; Infrastructure development; Great Plains; Kansas